Physiological maturity of seeds tung trees (Aleurites fordii Hemsl.) - Lima, Paulo Ricardo; Borsoi, Augustinho; dos Santos, Paulino Ricardo Ribeiro; Dranski, Joao Alexandre Lopes; Malavasi, Ubirajara Contro; Malavasi, Marlene de Matos (Revista de Ciências Agroveterinárias, 2016)
The test aimed to determine the physiological maturity of the seeds from tung nut trees (Aleurites fordii Hemsl.). Ten four-year-old fruits trees were collected in Cascavel - PR. The experiment followed a completely randomized design, with four fruit maturation stages and five replicates with 25 seeds each. The fruits were classified into three classes using the color of the epicarp and collected directly from the ground. To characterize the physiological maturity, digital colorimetric and biometric parameters were utilized. In seeds, the mass of dry matter, moisture content, germination and emergence speed index were determined. The seeds extracted from fruits with light brown eye color had higher dry matter, lower water content and percentage of germination and emergence rate, indicating the physiological maturity of seeds. Fruits collected from the ground are not suitable for seed collection. The harvest of the fruits to obtain seeds with physiological maturity is recommended when the fruits show light brown visual staining reflectance values in the visible spectrum (RGB) of 96.1, 69.9 and 64.1, respectively.